2021
DOI: 10.1155/2021/5555315
|View full text |Cite
|
Sign up to set email alerts
|

The Complementary and Alternative Medicine for Polycystic Ovary Syndrome: A Review of Clinical Application and Mechanism

Abstract: As a reproductive endocrine disease, polycystic ovary syndrome (PCOS) has influenced billions of women during childbearing age worldwide. Owing to its complex etiology and ambiguous pathogenesis, there is still not a specific method to cure it. Clinical treatments, such as hormone therapy and surgical treatment, have side effects. Therefore, it is essential and urgent to seek alternative treatment to solve these problems. The satisfactory efficacy of complementary and alternative medicine (CAM), such as tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 99 publications
0
12
0
Order By: Relevance
“…Some literature claims that pharmacologically based therapies are only effective in 60% of patients [ 64 ]. Recent studies have demonstrated that using complementary and alternative medicine (CAM) as adjunctive therapy may benefit the management [ 89 ]. Today, CAM is a well-known approach that has been used at least at one point in more than 70% of PCOS patients during their diseases [ 90 ].…”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Some literature claims that pharmacologically based therapies are only effective in 60% of patients [ 64 ]. Recent studies have demonstrated that using complementary and alternative medicine (CAM) as adjunctive therapy may benefit the management [ 89 ]. Today, CAM is a well-known approach that has been used at least at one point in more than 70% of PCOS patients during their diseases [ 90 ].…”
Section: Managementmentioning
confidence: 99%
“…One of the significant merits of CAM is that people often tend to accept these methods due to their beliefs and cultures; this leads to their improved adherence or tolerance to the therapy. Taking a look at prior studies, various methods of CAM including traditional Chinese medicine (TCM), immunotherapy, diet therapy (herbal and medicinal foods, probiotics, and vitamin or supplementation therapy), psychotherapy, spa, yoga, Tai Chi, and oxygen therapy have been considered as effective strategies in reducing the severity of PCOS and its complications [ 89 , 91 , 92 , 93 , 94 , 95 ]. Two critical subgroups of CAM effective in PCOS management are discussed in the following sections.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin resistance makes PCOS patients more vulnerable to long-term health issues like type 2 diabetes and cardiovascular disease, both of which can be fatal [ 7 ]. As a result, treating insulin resistance with medications and lifestyle modifications is essential for PCOS therapy [ 8 ].…”
Section: Reviewmentioning
confidence: 99%
“…Metformin usage over a long period has also been associated with vitamin B12 deficiency. Metformin has mild gastrointestinal side effects that can be prevented by starting with a modest dose of 500 mg and gradually rising to a maximum dose of 1500 mg once a week [ 8 ]. The most common symptoms are abdominal pain, diarrhoea, nausea, vomiting, and minor weight loss.…”
Section: Reviewmentioning
confidence: 99%